Pemanfaatan Daun Kelor dalam Pencegahan Stunting di Desa Lubuk Rumbai Kecamatan Tuah Negeri Kabupaten Musi Rawas - Fajar, Nur Alam; Ananingsih, Esti Sri; Hasyim, Hamzah; Flora, Rostika; Sulaningsi, Kiki; Rachmayanti, Riris Diana (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Stunting is a representation of chronic malnutrition throughout a time of growth and development from birth. Stunting can be caused by a variety of variables, including familial and toddler traits, as well as low dietary intake along with the prevalence of viral infections in children. This study intends to enhance housewives' understanding of preventing and overcoming stunting, as well as their abilities in using Moringa dodol maker (DOKERINA) for stunting prevention. The target in this service is mothers who visit the white jasmine Posyandu, totaling 30 people. This study used counseling methods and interactive discussions with the community, direct demonstrations on how to make Moringa dodol (Dokerina) by involving mothers at the posyandu, distribution of leaflets, administration of dokerina, cognitive tests. From the empowerment results, it was found that there was an increase in knowledge and skills, that is, the knowledge value increased by 37% from 60% to 97% and the skill value increased by 30% from 63% to 93%. It is hoped that related parties will continue to monitor the continuation of the Moringa dodol making program.